Seasick - Cast, Kristin; Dunn, Pintip (Delacorte Press, 2023)
While on a celebratory yacht trip to Bermuda, ex-best friends Naya and Yana, newly inducted into an exclusive society of top recent graduates, are plunged into a nightmare when a classmate is brutally murdered, and as the body count rises, they must team up to survive.